\section{Fibonacci} \definition{} The \textit{Fibonacci numbers} are defined by the following recurrence relation: \begin{itemize} \item $f_0 = 0$ \item $f_1 = 1$ \item $f_n = f_{n-1} + f_{n-2}$ \end{itemize} \problem{} Let $F(x)$ be the generating function that corresponds to the Fibonacci numbers. \par Find the generating function of $0, f_0, f_1, ...$ in terms of $F(x)$. \par Call this $G(x)$. \begin{solution} \begin{equation*} G(x) = xF(x) \end{equation*} \end{solution} \vfill \problem{} Find the generating function of $0, 0, f_0, f_1, ...$ in terms of $F(x)$. Call this $H(x)$. \begin{solution} \begin{equation*} H(x) = x^2F(x) \end{equation*} \end{solution} \vfill \problem{} Calculate $F(x) - G(x) - H(x)$ using the recurrence relation that we used to define the Fibonacci numbers. \begin{solution} \begin{align*} F(x) - G(x) - H(x) &=~ f_0 + (f_1 - f_0)x + (f_2 - f_1 - f_0)x^2 + (f_3 - f_2 - f_1)x^3 + ... \\ &=~ f_0 + (f_1 - f_0)x \\ &=~ x \end{align*} \end{solution} \vfill \pagebreak \problem{} Using the problems on the previous page, find $F(x)$ in terms of $x$. \begin{solution} \begin{align*} x &=~ F(x) - G(x) - H(x) \\ &=~ F(x) - xF(x) - x^2F(x) \\ &=~ F(x)(1-x-x^2) \end{align*} So, \begin{equation*} F(x) = \frac{x}{1-x-x^2} \end{equation*} \end{solution} \vfill \definition{} A \textit{rational function} $f$ is a function that can be written as a quotient of polynomials. \par That is, $f(x) = \frac{p(x)}{q(x)}$ where $p$ and $q$ are polynomials. \problem{} Solve the equation from \ref for $F(x)$, expressing it as a rational function. \begin{solution} \begin{align*} F(x) &=~ \frac{-x}{x^2+x-1} = \frac{-x}{(x-a)(x-b)} \\ &=~ \frac{1 - \sqrt{5}}{2\sqrt{5}}\frac{1}{x-a} + \frac{-1 - \sqrt{5}}{2\sqrt{5}}\frac{1}{x-b} \end{align*} where \begin{equation*} a = \frac{-1 + \sqrt{5}}{2} ;~~ b = \frac{-1 - \sqrt{5}}{2} \end{equation*} \end{solution} \vfill \pagebreak \definition{} \textit{Partial fraction decomposition} is an algebreic technique that works as follows: \par If $p(x)$ is a polynomial and $a$ and $b$ are constants, we can rewrite the rational function $\frac{p(x)}{(x-a)(x-b)}$ as follows: \begin{equation*} \frac{p(x)}{(x-a)(x-b)} = \frac{c}{x-a} + \frac{d}{x-b} \end{equation*} where $c$ and $d$ are constants. \problem{} Now that we have a rational function for $F(x)$, \par find a closed-form expression for its coefficients using partial fraction decomposition. \begin{solution} \begin{align*} F(x) &=~ \left(\frac{1 - \sqrt{5}}{2\sqrt{5}}\right)\left(\frac{-1}{a}\right)\left(\frac{1}{1-\frac{x}{a}}\right) + \left(\frac{-1 - \sqrt{5}}{2\sqrt{5}}\right)\left(\frac{-1}{b}\right)\left(\frac{1}{1-\frac{x}{b}}\right) \\ &=~ \left(\frac{1}{\sqrt{5}}\right)\left(\frac{1}{1-\frac{x}{a}}\right) + \left(\frac{-1}{\sqrt{5}}\right)\left(\frac{1}{1-\frac{x}{b}}\right) \\ &=~ \frac{1}{\sqrt{5}}\left(1 + \frac{x}{a} + \left(\frac{x}{a}\right)^2 + ...\right) - \frac{1}{\sqrt{5}}\left(1 + \frac{x}{b} + \left(\frac{x}{b}\right)^2 + ...\right) \end{align*} \end{solution} \vfill \problem{} Using problems from the introduction and \ref{pfd}, find an expression for the coefficients of $F(x)$ (and this, for the Fibonacci numbers). \begin{solution} \begin{align*} f_0 &= \frac{1}{\sqrt{5}} - \frac{1}{\sqrt{5}} = 0 \\ f_1 &= \frac{1}{a\sqrt{5}} - \frac{1}{b\sqrt{5}} = 1 \\ f_n &= \frac{1}{\sqrt{5}}\left(\frac{1}{a^n} - \frac{1}{b^n}\right) = \frac{1}{\sqrt{5}}\left( \left(\frac{1 + \sqrt{5}}{2}\right)^n - \left(\frac{1-\sqrt{5}}{2}\right)^n \right) \end{align*} \end{solution} \vfill \pagebreak \problem{Bonus} Repeat the method of recurrence, generating function, partial fraction decomposition, and geometric series to find a closed form for the following sequence: \begin{equation*} a_0 = 1 ;~~ a_{n+1} = 2a_n + n \end{equation*} \hint{ When doing partial fraction decomposition with a denominator of the form $(x-a)^2(x-b)$, you may need to express your expression as a sum of three fractions: $\frac{c}{(x-a)^2} + \frac{d}{x-a} + \frac{e}{x-b}$.`' } \vfill \pagebreak